2021
DOI: 10.21608/ttaip.2021.211518
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Analysis of Gender Representation in “Men vs. Women Memes”

Abstract: The ubiquity of the Internet has given rise to a plethora of new genres thus posing a problem for linguistic analysis which has long been focusing on verbal content. Internet memes are an emerging genre currently prevalent in computer mediated discourse (CMD). They constitute a new medium not only to deliver messages but also to create humor. A prototypical form of memes is the image macro meme, which typically consists of a still image with text superimposed so that their juxtaposition creates a humorous effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…By featuring women in group dynamics, the commercial aims to display a sense of unity, support, and shared experiences within the context of menstruation. This is in line with the findings of Mahfouz (2021) as he found that women tend to stick together and enjoy engaging in social activities as a collective [14]. This portrayal of women in group settings not only fosters a sense of community and solidarity but also promotes the idea of breaking societal barriers and empowering women to embrace their menstrual experiences.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…By featuring women in group dynamics, the commercial aims to display a sense of unity, support, and shared experiences within the context of menstruation. This is in line with the findings of Mahfouz (2021) as he found that women tend to stick together and enjoy engaging in social activities as a collective [14]. This portrayal of women in group settings not only fosters a sense of community and solidarity but also promotes the idea of breaking societal barriers and empowering women to embrace their menstrual experiences.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, verbal and visual communication often establish binary oppositions between genders perpetuating cultural stereotypes. These dichotomies reflect the underlying beliefs of each gender [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Egyptian meme creators construe a stereotypical image of the overbearing, aggressive mother who is responsible for every part and parcel of her house. On the surface, this new notion might seem revolutionary in comparison to the image of women in other studies (Machin and Thornborrow, 2006;Machin and van Leeuwen, 2007;Collins, 2011;El-Nashar and Nayef, 2014;Cuklanz, 2016, Abed andAl-Munshy, 2017;Tarabishi et al, 2017;Drakett et al, 2018;Lincoln, 2019;Abboud, 2020;Mahfouz, 2021); nevertheless, the analysis of the semiotic and thematic choices utilized in the memes denoted traces of the patriarchal system which still controls the lives of women. For example, when analyzing the symbolic attributes, the dominating symbol was the photoshopped colored veil which is edited into the majority of the memes.…”
Section: Discussionmentioning
confidence: 94%
“…Today, online memes can be defined as "viral images, videos, and catchphrases under constant modification by users, and with a propensity to travel as fast as the Internet can move them" (Coleman 2012, 109). The prototypical format of photo memes is composed of a still image and a superimposed text, thus, creating a humorous effect (Mahfouz, 2021). The memes can be schematized into two main categories: the recycled images which can virally evolve and serve as a template for further usage, and the other category is that of stable images which are shared without adaptions or transformations.…”
Section: Memes and Social Media Underpinningsmentioning
confidence: 99%
“…Motivated by their virality and ubiquity as the lingua franca of online communication and their unique aim that extends beyond inciting internet humor to become a form of "appropriation and resistance to dominant media messages", IMs became the subject of abundant research (Huntington 2013: 3;Nissenbaum and Shifman 2018). Different perspectives were adopted in researching this new genre such as the systemic perspective which investigates IMs as a system of signs representing a uniform movement in predetermined paths to cater for the netcitizens' expectations (Cannizzaro 2016 as cited in Zollinger 2021); the pragmatics perspective which concluded that the constative (for the expression of emotions) and the directive (for questioning issues) are the two main illocutionary acts by IMs (Nita, Setiawan and Lestari 2021); the multimodal pragmatics perspective which focuses on exploring the integration of semiotic resources for the interpretation and the construction of meaning (Mahfouz 2021); the generic perspective which foregrounds studying IMs' adherence to a template of specific generic rules (Dancygier and Vandelanotte 2017); finally, the cognitive perspective which studies the use of metaphors and metonymies in IMs (Younes and Altakhaineh 2022;Elyamany 2023). Nevertheless, there is a dearth of contrastive research across different languages on IMs as a genre marked by complex communication affordances in delivering meaning and creating humor.…”
Section: Introductionmentioning
confidence: 99%